Up-front cell-free DNA next generation sequencing improves target identification in UK first line advanced non-small cell lung cancer (NSCLC) patients. (August 2022) - Cui, Wanyuan; Milner-Watts, Charlotte; O'Sullivan, Hazel; Lyons, Hannah; Minchom, Anna; Bhosle, Jaishree; Davidson, Michael; Yousaf, Nadia; Scott, Sophie; Faull, Iris; Kushnir, Marina; Nagy, Rebecca; et al.
Abstract: Background: Genomic sequencing is necessary for first-line advanced non-small cell lung cancer (aNSCLC) treatment decision-making. Tissue next generation sequencing (NGS) is standard but tissue quantity, quality, and time-to-results remains problematic. Here, we compare upfront cell-free-DNA (cfDNA) NGS clinical utility against routine tissue testing in patients with aNSCLC. Methods: cfDNA-NGS was performed in consecutive, newly identified aNSCLC patients between December 2019–October 2021 alongside routine tissue genotyping. Variants were interpreted using AMP/ASCO/CAP guidelines. The primary endpoint was tier-1 variants detected on cfDNA-NGS. cfDNA-NGS results were compared to tissue results. Results: Of 311 patients, 282 (91%) had an informative cfDNA-NGS test; 118 (38%) patients had a tier-1 variant identified by cfDNA-NGS. Of 243 patients with paired tissue-cfDNA tests, 122 (50%) tissue tests were informative; 85 (35%) tissue tests identified a tier-1 variant. cfDNA-NGS detected 39 additional tier-1 variants compared to tissue alone, increasing the tier-1 detection rate by 46% (from 85 to 124). The sensitivity of cfDNA-NGS relative to tissue was 75% (25% tissue tier-1 variants were not detected on cfDNA-NGS); 33% of cfDNA tier-1 variants were not identified on tissue tests. Median time from request-to-report was shorter for cfDNA-NGS versus tissue (8 versus 22 days; p < 0.0001). A total of 245 (79%) patients received first-line systemic-therapy: 49 (20%) with cfDNA-NGS results alone. Median time from sampling-to-commencement of first-line treatment was shorter for cfDNA-NGS blood draw versus first tissue biopsy (16 versus 35 days; p < 0.0001). Conclusions: cfDNA-NGS increased the tier-1 variant detection rate with high concordance with tissue, and halves time-to-treatment. 'Plasma-first' upfront cfDNA-NGS use should be considered routinely for aNSCLC. Highlights: cfDNA-NGS enabled rapid detection of tier 1 genomic variants in advanced NSCLC. cfDNA-NGS increased the detection rate of tier 1 variants by 46% versus tissue alone. The sensitivity of cfDNA-NGS relative to paired tissue tests was 75%. Time from request to report was shorter for cfDNA-NGS versus standard tissue tests. Time from sampling to treatment initiation was shorter for cfDNA-NGS versus tissue.